Polyethylenimine, an Autophagy-Inducing Platinum-Carbene-Based Drug Carrier with Potent Toxicity towards Glioblastoma Cancer Stem Cells - McCartin, Conor; Dussouillez, Candice; Bernhard, Chloé; Mathieu, Eric; Blumberger, Juliette; Dontenwill, Monique; Herold-Mende, Christel; Idbaih, Ahmed; Lavalle, Philippe; Bellemin-Laponnaz, Stéphane; Kichler, Antoine; Fournel, Sylvie (Cancers, 2022)
The difficulty involved in the treatment of many tumours due to their recurrence and resistance to chemotherapy is tightly linked to the presence of cancer stem cells (CSCs). This CSC sub-population is distinct from the majority of cancer cells of the tumour bulk. Indeed, CSCs have increased mitochondrial mass that has been linked to increased sensitivity to mitochondrial targeting compounds. Thus, a platinum-based polyethylenimine (PEI) polymer-drug conjugate (PDC) was assessed as a potential anti-CSC therapeutic since it has previously displayed mitochondrial accumulation. Our results show that CSCs have increased specific sensitivity to the PEI carrier and to the PDC. The mechanism of cell death seems to be necrotic in nature, with an absence of apoptotic markers. Cell death is accompanied by the induction of a protective autophagy. The interference in the balance of this pathway, which is highly important for CSCs, may be responsible for a partial reversion of the stem-like phenotype observed with prolonged PEI and PDC treatment. Several markers also indicate the cell death mode to be capable of inducing an anti-cancer immune response. This study thus indicates the potential therapeutic perspectives of polycations against CSCs.
Gesehen am 11.01.2023